Teknik Menulis Naskah Dakwah Untuk Berbagai Tema Aqidah, Akhlaq dan Syariah - Azizah, Sayidatul (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
Writing a dakwah (Islamic preaching) script requires specific skills to ensure that the message is well-understood, accepted, and practiced by the audience. This article discusses effective techniques for writing dakwah scripts on various themes, including aqidah (Islamic creed), akhlaq (morality), and sharia (Islamic law). The research method used is a literature review and descriptive analysis of various dakwah script examples. The findings indicate that a well-written dakwah script should meet several key criteria: alignment with Islamic teachings (Al-Qur'an and Hadith), communicative language, and a systematic and persuasive structure. In drafting a script on aqidah, strong and rational arguments are necessary to strengthen the audience’s faith. Meanwhile, scripts on akhlaq should focus on emotional appeal and concrete examples to inspire behavioral change. For sharia-related topics, it is essential to provide clear textual evidence and practical applications of Islamic law in daily life. Moreover, adapting the content to the audience’s characteristics significantly impacts the effectiveness of the message. Therefore, a dakwah scriptwriter must identify the audience's needs and select an appropriate language style. By applying the right writing techniques, dakwah scripts can serve as a powerful tool for spreading Islamic values broadly and profoundly.